Elite junior Australian football players with impaired wellness are at increased injury risk at high loads - Lathlean, T. J. H.; Newstead, S. V.; Gastin, P. B. (Sports Health: A Multidisciplinary Approach, 2023)
Background: Elite junior Australian football players experience high training loads across levels of competition and training. This, in conjunction with impaired wellness, can predispose athletes to injury.